Introduction of enhanced recovery for elective caesarean section enabling next day discharge: a tertiary centre experience. Issue 2 (May 2015) - Wrench, I.J.; Allison, A.; Galimberti, A.; Radley, S.; Wilson, M.J.
Highlights We introduced an enhanced recovery programme for elective caesarean section to our unit. We used simple, easily generalisable interventions. The proportion of women going home the day after surgery increased from 1.6% to 25.2%. The readmission rates for women leaving on days one and two were similar. Length of stay was influenced by multiple birth, breast feeding, times for surgery and recovery and indication for surgery.